Can pretreatment lactate dehydrogenase to albumin ratio predict pathological complete response after neoadjuvant chemotherapy in breast cancer patients? - Savaş, Gözde; Günel, Nazan; Özet, Ahmet (Journal of Medical Biochemistry, 2025)
Background: The aim of this study is to evaluate the predictive significance of platelet lymphocyte ratio (PLR), neutrophil lymphocyte ratio (NLR), lymphocyte monocyte ratio (LMR), systemic immune-inflammation (SII), prognostic nutritional index (PNI), The hemoglobin, albumin, lymphocyte, and platelet (HALP) score and lactate dehydrogenase to albumin ratio (LAR) for pCR in breast cancer with neoadjuvant chemotherapy (NACT). Methods: A total of 121 patients who received NACT between February 2012 and November 2021 were included. LAR, NLR, PLR, MLR, SII, PNI and HALP were calculated according to formulas. The cut-off value for markers were obtained by Receiver operating characteristic curve (ROC) analyses. Independent predictive factors for pCR were determined using multivariate regression analysis. Results: The pCR rate was achieved in 31.4% of patients. Median values of NLR, PLR, MLR, SII, PNI and HALP were similar in pCR (+) and pCR (-) (p > 0.05). Median LAR value was significantly higher in pCR (+) than pCR (-) (50.80 vs 42.62, respectively (p=0.002)). The optimal cutoff value of LAR was 46.27. Multivariate analysis showed that LAR ³46.27 and HER-2 positivity were the independent predictive factors for pCR [OR = 2.851 (95% CI = 1.142-7.119, P = .025), OR = 3.431 (95% CI = 1.163-10.123, P = 0.026), respectively]. Conclusion: LAR is a simple, inexpensive, and convenient method for predicting pCR in breast cancer with NACT.